Review of Standardization of Parking Area Markings at Aji Pangeran Tumenggung Pranoto Airport, Samarinda - Sultan Aqilla Ahmad Napitupulu; Hemi Pamuraharjo; Dini Wagini (FTK UNSURYA, 2026)
The rapid growth of flight operations at Aji Pangeran Tumenggung Pranoto Airport in Samarinda has raised concerns regarding the standardization and effectiveness of parking stand markings on the apron, which are crucial for ensuring safety and efficiency. This study aims to evaluate and redesign the standardization of parking stand markings to address these concerns. Field findings during On-the-Job Training (OJT) revealed several issues, including inconsistencies in Stopline Marking placements, discrepancies between parking stand data and the Aeronautical Information Publication (AIP), as well as the deterioration of markings due to weather exposure and apron vehicle movement. This research adopts a qualitative descriptive approach with triangulation of observation, interviews, and document review to ensure the validity of findings. Results suggest the need for corrective measures such as repainting faded markings, repositioning Stopline Markings for better visibility and accuracy, and updating parking stand coordinates in the AIP. Implementing these improvements is expected to enhance apron operational safety and align with Regulation PR 21 of 2023 and internationally recognized aviation standards.